Perempuan dan Perjuangannya: Double Burden dan Konsistensi Perempuan Penjual Makanan dalam Meningkatkan Kesejahteraan Keluarga di Majalengka - Nurlaili Khikmawati; Muhammad Alief Yazidal Bustomi; Yayat Suryatna (Islamic Management and Empowerment Journal, 2024)
This research explores the roles, challenges, and strategies of female food traders in improving family welfare in Sadomas Village, Rajagaluh District, Majalengka. Despite their significant contribution to the family economy, women’s position in Indonesian society is often considered secondary due to their role as domestic creatures. The study uses qualitative research methods, including direct observation, semi-structured interviews, and documentation, and analyzes the collected data using Miles & Huberman’s techniques. The results show that women selling food in Sadomas Village can improve family welfare through domestic, productive, and social roles. However, they face challenges such as double burdens and time management. To overcome these challenges, they implement internal and external strategies such as managing finances, prioritizing business capital, reducing food quantity when prices rise, and arranging holiday time. They also utilize financial services and involve families in supporting children’s work, health, and education